2011
DOI: 10.3928/01477447-20110427-16
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Management of Stiff Elbow

Abstract: Elbow stiffness is a common problem encountered by orthopedic surgeons. Various management options have been described in the literature, including conservative measures and open and arthroscopic surgery. Arthroscopic management of stiff elbow remains controversial. The purpose of this study was to evaluate the functional results of arthroscopic management of stiff elbow.Thirty patients with stiff elbow underwent arthroscopic release surgery and were followed up for an average of 27.3 months. Surgery included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…The improvement in postoperative arc of motion found in this study is similar to the amount of improvement reported by previous investigators, which tends to average around 50°. 1 , 7 , 8 , 10 The significant improvement in pronation and supination after arthroscopic capsular release found in this study has also been reported by other studies. 1 , 2 , 8 , 10 Schreiner et al 8 reported an improvement of 18% in pronation and supination after arthroscopic elbow capsular release, while the mean improvement of 4.4° (5.4%) pronation and 6.1° (7.7%) supination found in this study is lower than this reported value.…”
Section: Discussionsupporting
confidence: 90%
“…The improvement in postoperative arc of motion found in this study is similar to the amount of improvement reported by previous investigators, which tends to average around 50°. 1 , 7 , 8 , 10 The significant improvement in pronation and supination after arthroscopic capsular release found in this study has also been reported by other studies. 1 , 2 , 8 , 10 Schreiner et al 8 reported an improvement of 18% in pronation and supination after arthroscopic elbow capsular release, while the mean improvement of 4.4° (5.4%) pronation and 6.1° (7.7%) supination found in this study is lower than this reported value.…”
Section: Discussionsupporting
confidence: 90%
“…In most of the cases, some form of modalities, such as ultrasonic heat and physiotherapy along with anti-inflammatory medications improves the ROM. But in severe elbow stiffness surgery is generally needed [31].…”
Section: • Stiff Elbowmentioning
confidence: 99%
“…Manipulation under anesthesia after inflating the joint with saline can be done in a controlled manner in less severe contractures. But it is a risky procedure with complications such as muscle tear, fractures, neurovascular, and ligament injury [30,31].…”
Section: • Stiff Elbowmentioning
confidence: 99%
See 1 more Smart Citation
“…bow 13,14 because a stiff elbow capsule has considerably less capacity and compliance than a capsule in a normal elbow, thereby increasing the potential neurovascular injury in elbow arthroscopy. 15 Advocates of a lateral approach claim some advantages, such as less risk of nerve damage and fewer wound complications.…”
Section: A 1bmentioning
confidence: 99%